Genetic Variation of Salt Tolerance Characterand Organic Components Studies in Selected Salt Tolerant Genotypeand Sensetive Cultivar of Wheat (Global Journal of Science Frontier Research, 2015)
Genetic evaluation was estimated for salt tolerance between the selected wheat genotype through plant breeding program and local cultivar by using random amplified polymorphic DNA (RAPD-PCR reaction) with two selected primers (OP1-01 and GB8). According to the amplification results, the genetic distance, Dendrogram illustrated genetic fingerprint and relationships between the selected genotype (Dijila) and local cultivar (Tamooze-2) were determent under non and saline condition. Also the chlorophyll content and organic compounds of the upper leaves were measured.
Keywords: wheat; salt tolerance; RAPD-RCR reaction; chlorophyll; organic compounds